Community pharmacist intervention in doxycycline self-medication for acne among pregnant women in Saudi Arabia - Marwan Alrasheed; Wael Hamdy Mansy; Mohamed Naser Al-Arifi (Elsevier, 2024)
Introduction: Self-medication during pregnancy remains a prevalent global phenomenon, with pregnant women often relying on their own judgment to manage symptoms. Objective: This study aimed to assess community pharmacist practice regarding self-medication requests for acne treatment in pregnant women within Saudi Arabia. Methods: A descriptive, observational cross-sectional study was conducted in Riyadh, Saudi Arabia. Community pharmacists completed a questionnaire after interacting with a simulated customer (SC) seeking doxycycline for a pregnant woman. Data were analyzed using SPSS software. Results: One hundred community pharmacists participated in the study. The majority were between 25 and 35 years old (56 %) and worked in chain pharmacies (81 %). Notably, 71 % requested a prescription before dispensing any medication. While 66 % advised the SC to consult a physician or dermatologist, only 15 % inquired about the pregnancy and related information of the SC's sister. Conclusion: This study suggests a positive trend in community pharmacy practice regarding self-medication requests during pregnancy. However, further improvement is needed, particularly in terms of in-depth inquiry about pregnancy status and potential risks associated with specific medications. Collaborative efforts between the Ministry of Health (MOH), Saudi Food and Drug Administration (SFDA), and pharmacy education programs are crucial to minimize inappropriate dispensing practices and ensure optimal patient safety.